2018
DOI: 10.1620/tjem.245.69
|View full text |Cite
|
Sign up to set email alerts
|

Altered Wnt and NF-<i>κ</i>B Signaling in Facet Joint Osteoarthritis: Insights from RNA Deep Sequencing

Abstract: Facet joint osteoarthritis is common lumbar osteoarthritis characterized by facet joint cartilage degeneration. However, the molecular basis of facet joint osteoarthritis remains largely undetermined. In the current study, we collected facet joint tissue samples from 10 control patients and 48 patients with facet joint osteoarthritis (20 patients with moderate degeneration and 28 with severe degeneration). The control patients underwent internal fixation of the lumbar spine due to vertebral fracture. RNA deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
(31 reference statements)
4
18
0
1
Order By: Relevance
“…Production of CCL7 from synoviocytes is enhanced by IL-17 [41]. Patients with facet joint osteoarthritis (n = 48) also demonstrated elevated CCL4 and C-C Motif Chemokine Ligand 4 Like 2 (CCL4L2) compared to healthy controls (n = 10) [64]. The study showed that CCL4 and CCL4L2 expressions were involved in the canonical NF-κB signaling pathway.…”
Section: The Role Of Chemokines In Osteoarthritismentioning
confidence: 87%
“…Production of CCL7 from synoviocytes is enhanced by IL-17 [41]. Patients with facet joint osteoarthritis (n = 48) also demonstrated elevated CCL4 and C-C Motif Chemokine Ligand 4 Like 2 (CCL4L2) compared to healthy controls (n = 10) [64]. The study showed that CCL4 and CCL4L2 expressions were involved in the canonical NF-κB signaling pathway.…”
Section: The Role Of Chemokines In Osteoarthritismentioning
confidence: 87%
“…Their subsequent functional study suggested that lncRNA uc.217 could regulate neurite outgrowth and lncRNA TNXA-PS1 could regulate Schwann cell migration. [19][20][21] In the current work, by using RNA deep sequencing, we identied a total of 37 488 lncRNAs in facet joints. By comparing the expression levels of these lncRNAs in patients with control facet joints and patients with FJOA, a total of 8506 differentially expressed lncRNAs were discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the most differentially expressed genes in FJOA. Previous transcriptome sequencing determined the expression levels of >19,000 genes in human facet joint tissues in both FJOA and control groups (15). To obtain a global view of the expression patterns of identified genes, the Heatmap function in the software platform R (v.2.13.0) was used to draw a heatmap of gene expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human facet joint tissues were collected from 48 patients with FJOA (FJOA group) and 10 healthy patients with vertebral fractures (control group) as previously described (15). Magnetic resonance imaging was applied to determine the degree of cartilage degeneration.…”
Section: Facet Joint Tissue Collection and Transcriptome Sequencingmentioning
confidence: 99%
See 1 more Smart Citation